2006
DOI: 10.1111/j.1365-2222.2005.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of allergen challenge chambers in the evaluation of anti‐allergic medication: an international consensus paper

Abstract: Summary Allergic rhinitis (AR) is a common condition with quality of life and economic implications for those affected. Numerous studies have attempted to evaluate treatments for rhinitis, seeking clinically meaningful efficacy and safety results to enable evidence‐based treatment decisions. Traditional studies of medications for AR are hampered by many confounding environmental factors as well as suboptimal medication compliance. They are also an unsuitable setting for determination of precise pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 117 publications
2
39
0
2
Order By: Relevance
“…Clinical exposure studies of grass pollen often use concentrations in the range 1000-8000 grains m −3 (Day et al, 2006) -about a factor of 10 larger than what is found in typical peak observations. These levels are chosen to obtain a clear signal from the patients used in the exposure studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical exposure studies of grass pollen often use concentrations in the range 1000-8000 grains m −3 (Day et al, 2006) -about a factor of 10 larger than what is found in typical peak observations. These levels are chosen to obtain a clear signal from the patients used in the exposure studies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an environmental exposure chamber (EEC) allows for clinical trial subjects to be exposed to aeroallergens in a highly controlled manner and allows the use of pre-established allergen levels known to induce symptoms at the moderate-to-severe level. 9,10 In a previous unrelated pilot EEC study we demonstrated that treatment with a 3-nmol dose of Cat-PAD with 4 or 8 injections over a 12-or 14-week period resulted in a greater reduction in mean total rhinoconjunctivitis symptom scores (TRSSs) than placebo, with a mean treatment difference of 2.9 units between 1 and 3 hours on days 2 and 4 of consecutive 3-hour EEC challenges 17 to 21 weeks after the start of treatment. 11 Abbreviations used AE: Adverse event EEC: Environmental exposure chamber PAD: Peptide antigen desensitization PTC: Posttreatment challenge TEAE: Treatment-emergent adverse events TNSS: Total nasal symptom score TOSS: Total ocular symptom score TRSS: Total rhinoconjunctivitis symptom score…”
mentioning
confidence: 97%
“…An ACC is a specially designed room used to expose study participants to a fixed, predetermined allergen concentration for a set period of time. 6 ACCs also allow identical repeated exposures and thus assessment of changes over time in an individual's response.…”
mentioning
confidence: 99%